Analiza vpliva čustvene inteligence zaposlenih na uspešnost delovanja organizacije - Vukasovič, Tina (Management, 2013)
Modern company needs as the foundation of its successful operation clearly dened vision, employees values and high, but still reachable business goals, which are based on high level involvement of employees in the company and on the basis of their participation. Knowledge, skills and experience, that employees possess, are strong arguments of successful company, but it is not all the same, with what kind of emotions arguments are expressed in their own practice. Research shows that emotional intelligence respondents attach great inuence in the success of the company. Emotional intelligence should help both to better work performance, as well as to improve the physical well-being and emotional stability.
Keywords: čustvena inteligentnost; empatija; knowledge; poslovna uspešnost; zaposleni; znanje